FORMING THE QUALITY OF CREATIVITY IN STUDENTS BY TEACHING THE LIFE AND WORK OF COMPOSER SULAYMON YUDAKOV - M.Djumaboyeva (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, the life path and works of composer S. Yudakov, who contributed to the achievement of certain achievements in the art of music, were discussed in the study of the work of composers and composers in Uzbek music culture.